Peculiarities of changes in latent periods of sensor motor responses in young athletes aged 13-16 years depending on the orientation of their training process. - Khoroshukha M.F (Kharkov National Pedagogical University, 2012)
It is shown peculiarities of the specific impact of various types of training loads on the body of young athletes. In experiment involved 263 young athletes engaged in different sports (group A- speed-strength sports, group B-endurance sports) and 62 secondary school pupils, who don't go in for sports, aged of 13-16 years. A technique of psycho-physiological research was considered. A comparative analysis of changes in rates of psycho-physiological reactions of the surveyed studies for data research'80s and 2000s is shown. It is established that the specificity of the training process is reflected in the nature of the changes of the latent period of simple and complex sensor motor reactions that have the majority of cases are genetically determined. Substantiated the importance of changes in these parameters in the practice of physical education.